Dune Restoration and Enhancement for the Florida Panhandle - Debbie L. Miller; Mack Thetford; Chris M. Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Published by the UF/IFAS Florida Sea Grant College Program, this manual provides an overview of the coastal ecosystems along the Florida Panhandle and shows how dunes can be restored and enhanced in this region of the Northern Gulf of Mexico.